Analysis of snowboard stiffness and camber properties for different riding styles - Subic, A.; Clifton, P.; Beneyto-Ferre, J.; LeFlohic, A.; Sato, Y.; Pichon, V. (The Engineering of sport 7, Volume 1, 2008)
Research has indicated that the flex pattern and camber of a snowboard are crucial to its overall "feel" and response. These features are the primary cause of Variation in snowboard performance for different riding styles. Consequently, this article deals with the identification of stiffness and camber characteristics for both freestyle and freeride boards, and their statistical correlation to a comprehensive list of qualitative "feel" based performance requirements.